Elektroforesis: Analisis Elektronika Terhadap Biokimia Genetika - Muhammad Ridwan Harahap (PTE FTK UIN Ar-Raniry, 2018)
Electrophoresis is a method of separation that utilizes the electric field generated from electrodes to separate compounds having a charge of cations or anions. Electrophoresis requires separation media in the form of a stationary phase such as Agarose cells mixed with a buffer solution to maintain the acidity of the sample during the separation process. This tool strongly supports the renewal of research, especially in the field of genetic engineering technology. The result will provide a track record of separation bands of compounds. The speed of molecular motion depends on the ratio (ratio) of charge to its mass, and also depends on the shape of the molecule.